Physicochemical and rheological properties of palm-milk cheese analog using starches from different Malaysian rice cultivars - Joh, Xin Yee; Mohsin, Aliah Zannierah; Marzlan, Anis Asyila; Meor Hussin, Anis Shobirin; Shukri, Radhiah; Berahim, Zulkarami; Abd Rahim, Muhamad Hafiz; Sukor, Rashidah (Hibiscus Publisher Enterprise, 2024)
The development of new rice varieties in Malaysia (NMR and Putra 2) has presented the need to characterize their techno-functional properties in food production. Starch, a main component of rice, has been applied in developing plant-based cheese analogs to mimic the textural characteristics of conventional dairy cheese. This study aimed to determine the effect of different types of starch on the physicochemical, textural, and thermal properties of palm milk cheese analog (PMCA). A total of 4 samples were produced with 0% starch as negative control (Sample A), 2% Putra 2 rice starch (B), 2% NMR rice starch (C), and 2% corn starch as positive control (D). The samples were subjected to physicochemical analyses of water activity, pH, titratable acidity, colour. Results indicated that PMCA showed greater storage moduli than the loss moduli representing dense interlinked weak gels supported by a less compact structure, and a rough surface was observed in the microstructure of samples with starch. In conclusion, the incorporation of different types of starches had a significant effect on the rheological properties of the PMCAs while having no significant differences on their physicochemical properties.